Grounding an Integrative Paradigm in Reading and Interpreting Hadith Based on Scientific Approaches: Membumikan Paradigma Integratif dalam Membaca dan Menafsirkan Hadis melalui Pendekatan Ilmiah - Baiq Mira Nurfatihah; Churun Jauharoh Al Aryachiyah; Ahmad Ubaidillah Ma'sum Al Anwari (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The issue of modernity has exerted a considerable influence on contemporary life, particularly through the persistent epistemological dichotomy that separates religion and science. This binary opposition fundamentally contradicts religious principles that serve as comprehensive guides for human life, especially given the numerous Prophetic traditions (hadith) that explicitly address scientific realities. This article examines integrative methodological approaches bridging hadith studies and scientific inquiry, framed by two primary research questions: First, what constitutes a scientific approach in hadith scholarship? Second, to what extent can scientific methodology be applied in interpreting, comprehending, and deriving meaning from hadith texts? Employing qualitative library research methodology, this study demonstrates the critical importance of an integrative approach in addressing complex contemporary issues that transcend traditional halal-haram juridical frameworks. The findings reveal that scientific approaches to hadith studies make significant contributions to expanding religious discourse beyond its conventional doctrinal-immanent limitations. As this methodology gains broader acceptance, hadith literature is progressively liberated from perceptions of rigid normativity or obsolescence, emerging instead as a dynamic intellectual tradition capable of substantive engagement with modern epistemological developments.